Germline genetic variability in pancreatic cancer risk and prognosis. (February 2022) - Gentiluomo, Manuel; Canzian, Federico; Nicolini, Andrea; Gemignani, Federica; Landi, Stefano; Campa, Daniele
Abstract: Pancreatic cancer (PC), particularly its most common form, pancreatic ductal adenocarcinoma (PDAC), is relatively rare but highly lethal. Knowledge about PC risk factors could in the long term contribute to early diagnosis and mortality reduction. We review the current status of research on germline genetic factors for PC risk. Genome-wide association studies (GWAS) successfully identified common loci convincingly associated with PC risk, an endeavor that is still ongoing. The function of only a handful of risk loci has being thoroughly characterized so far. Secondary analyses of existing GWAS data are being used to discover novel loci. GWAS data have also been used to study additional risk factors with a Mendelian randomization approach. Polygenic/multifactorial risk scores show much larger risks than individual variants, but their use for risk stratification in the population is not warranted yet. At the other end of the spectrum of inherited PC risk factors, rare high-penetrance variants co-segregating with the disease have been observed in familial cancer syndromes that include PC, or in families with multiple recurrence of PC alone. Rare variants predicted to have a deleterious effect on function are studied also with a case-control approach, by resequencing candidate genes or whole-exomes/whole-genomes. Telomere length and mitochondrial DNA copy number are useful additional DNA-based markers of PC susceptibility. The role of common variants in prognosis of PC patients has also been explored, albeit with more limited success than risk. Finally, genetics of pancreatic neuroendocrine tumors (PNET), a rarer and heterogeneous form of PC, is still understudied.